Pelatihan Penyusunan Laporan Keuangan Berdasarkan Peraturan Perpajakan UMKM Pada CV Tirta Sasmita Universitas Pamulang - Listiya Ike Purnomo; Rosita Wulandari; Effriyanti Effriyanti (Abdimisi, 2021)
The existence of micro, small and medium enterprises (MSMEs) should no longer be underestimated. This is because MSMEs are a new economic source for Indonesia's development. MSMEs are encouraged to improve the quality and quantity of their products. CV Tirta Sasmita is a company engaged in the production of mineral water, CV Tirta Sasmita is a form of business organized by Pamulang University as a forum for practical learning for Pamulang University students and is expected to be a center of excellence for the Unpam academic community. Currently, CV Tirta Sasmita produces cup, refilled gallon, and bottled drinking water. This PKM aims to provide assistance for tax calculations on CV Tirta Sasmita. The method used in this activity is the mentoring method. The materials provided during the training and mentoring include: (1) the importance of calculating taxes for MSMEs, (2) how to calculate corporate income tax. Taxes are not only an obligation, but are the right of every citizen to participate in the form of participation in state financing and development. Through this PKM activity, it is hoped that the Accounting Study Program can implement accounting knowledge, especially in the field of tax calculations, and increase MSME awareness of taxes in Indonesia.